The map of vegetation complexes of the Seili island and its surroundings (SW Finland) - Wojterska, Maria; Balcerkiewicz, Stanisław; Brzeg, Andrzej (Biodiversity: Research and Conservation, 2018)
The paper gives the results of studies on vegetation complexes of 12 islands and several skerries, situated within the inner part of SW Finnish archipelago. There were differentiated 14 types of complexes, comprising all types of communities (of vascular plants, mosses and lichens). All complexes are characterised by a repetitive combination of communities. Their distribution, showing distinct regularities in relation to geology, geomorphology and situation on an island, is depicted in the map.